2012
DOI: 10.1016/j.physa.2011.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of financial markets in times of crisis

Abstract: Using the eigenvalues and eigenvectors of correlations matrices of some of the main financial market indices in the world, we show that high volatility of markets is directly linked with strong correlations between them. This means that markets tend to behave as one during great crashes. In order to do so, we investigate financial market crises that occurred in the years 1987 (Black Monday), 1998 (Russian crisis), 2001 (Burst of the dot-com bubble and September 11), and 2008 (Subprime Mortgage Crisis), which m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(123 citation statements)
references
References 128 publications
12
110
0
1
Order By: Relevance
“…Forbes and Rigobon 13 have shown that a high level of dependence is visible between most markets, and that changes in correlation are coupled to volatility changes. A more multidisciplinary analysis of the correlation between the indices of different markets can be found for example in the recent study of Song et al 14 , and of Sandoval et al 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Forbes and Rigobon 13 have shown that a high level of dependence is visible between most markets, and that changes in correlation are coupled to volatility changes. A more multidisciplinary analysis of the correlation between the indices of different markets can be found for example in the recent study of Song et al 14 , and of Sandoval et al 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Using stock market data from Coletti and Murgia (2015), which starts in 1973, we can also study the network's topology during past decades' crises like Sandoval and Franca (2012) and Sandoval (2012b) to identify common stock market's patterns across different economic cycles. Moreover, since MST tends to hide some important relations and does not display cliques while the full network is difficult to visualize, we could analyze the network using other alternative methods, such as planar graph PMFG (Coronnello et al, 2005;Tumminello et al, 2005) or MST with cliques (Onnela et al, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…Sharp growth of volatility signals about increase of the panic moods in the stock market and allows to detect crisis phases (Crato & Ray, 2000;Kazemi, 2013). The growth of correlations between various assets in the stock market signals about the emergence of crisis phenomena in financial and economic systems (Sandoval & Franca, 2012), the same is true for the market persistence (Caporale et al, 2016).…”
Section: Introductionmentioning
confidence: 91%